2001
DOI: 10.1677/joe.0.1690097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate on expression of members of the IGF-binding protein superfamily in human mammary epithelial cells

Abstract: Dietary factors play an important role in both the development and prevention of human cancers, including breast carcinoma. One dietary micronutrient, sodium butyrate (NaB), is a major end product of dietary starch and fiber, produced naturally during digestion by anaerobic bacteria in the cecum and colon. NaB is a potent growth inhibitor and initiates cell differentiation for many cell types in vitro. In this study, we investigated the effects of NaB on three human mammary epithelial cells and regulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 52 publications
2
20
0
3
Order By: Relevance
“…MCT1 is known as a cellular transporter of monocarboxylates, including butyrate [32, 33]. Since butyrate plays important roles in the differentiation of mammary epithelial cells [34, 35], the downregulation of its transporter could confer a growth advantage to mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MCT1 is known as a cellular transporter of monocarboxylates, including butyrate [32, 33]. Since butyrate plays important roles in the differentiation of mammary epithelial cells [34, 35], the downregulation of its transporter could confer a growth advantage to mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In these last conditions, the actions of butyrate are believed to involve the hormononeuro-immunosystem (Guilloteau et al 2010a). As examples, it was suggested that Na-butyrate may act through growth factors (Tsubaki et al 2001) or endocrine systems (Simon et al 1997, Bartholome et al 2004, Katoh et al 2007). Na-butyrate may also stimulate defence systems through heat shock proteins and modify immune and inflammatory responses (Ren et al 2001, Millard et al 2002, Böcker et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in rats, Na-butyrate infusion into the lumen of the large intestine stimulated the mucin secretion (Barcelo et al, 2000). Finally, it was shown that Na-Butyrate is implicated in gene expression (Tsubaki et al, 2001;Böker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%